The Role of Social Marketing in Popularizing Kurdish Characters (Raparin Journal of Humanities (RJH), 2025)
The main purpose of this research is to try to understand the role of Kurdish characters through social marketing in order to make them famous, through the participation of a number of academics and experts in the fields related to social marketing in order to understand and know it The relationship between these two aspects, social marketing and popularization of Kurdish characters, the study works to identify the mechanisms and different methods used in social marketing to achieve this goal, as well as showing the role of new ideas New In this context, one of the important objectives of this study is to identify the negative consequences of social marketing that result from attempts to popularize Kurdish characters. The study finally obtained several results, the most important of which, according to the test (T-test) for (social marketing) is (14.113) and the value of evidence level (0.000) appears (social marketing (has an effect on (naming Kurdish characters). R2 -) which is (0.448) or (44.8%) reflects the level of (social marketing) has an impact on (naming Kurdish characters).